Capillary electrophoresis, a method for the determination of nucleic acid ligands covalently attached to quantum dots representing a donor of Förster resonance energy transfer - Datinská, Vladimíra; Klepárník, Karel; Belšánová, Barbora; Minárik, Marek; Foret, František (Journal of separation science, 2018)
The synthesis and determination of the structure of a Förster resonance energy transfer probe intended for the detection of specific nucleic acid sequences are described here. The probe is based on the hybridization of oligonucleotide modified quantum dots with a fluorescently labeled nucleic acid sample resulting in changes of the fluorescence emission due to the energy transfer effect. The stoichiometry distribution of oligonucleotides conjugated to quantum dots was determined by capillary electrophoresis separation. The results indicate that one to four molecules of oligonucleotide are conjugated to the surface of a single nanoparticle. This conclusion is confirmed by the course of the dependence of Förster resonance energy transfer efficiency on the concentration of fluorescently labeled complementary single-stranded nucleic acid, showing saturation. While the energy transfer efficiency of the probe hybridized with complementary nucleic acid strands was 30%, negligible efficiency was observed with a noncomplementary strand.
Keywords: sensors; Förster resonance energy transfer; capillary electrophoresis; quantum dots; nucleic acids